UVA‐1 phototherapy as adjuvant treatment for eosinophilic fasciitis: in vitro and in vivo functional characterization. (8th December 2021) - Tognetti, Linda; Marrocco, Camilla; Carraro, Andrea; Conticini, Edoardo; Habougit, Cyril; Mariotti, Giancarlo; Cinotti, Elisa; Perrot, Jean Luc; Rubegni, Pietro
Abstract: Introduction: Eosinophilic fasciitis (EF) is a rare autoimmune disease causing progressive induration of dermal, hypodermal, and muscularis fascia. The exact pathogenesis is yet to be fully understood, and a validated therapy protocol still lacks. We here aimed to realize a clinical–functional characterization of these patients. Materials and methods: A total of eight patients (five males, 45 years average) were treated with adjuvant high‐dose UVA‐1 phototherapy (90 J/cm), after having received the standard systemic immunosuppressive protocol (oral methylprednisolone switched to methotrexate). Body lesion mapping, Localized Scleroderma Assessment Tool (LoSCAT), Dermatology Life Quality Index (DLQI), High‐Resolution Ultrasound (HRUS) (13‐17MHz), and ultra HRUS (55–70 MHz) were performed at each examination time taking specific anatomical points. Gene expression analysis at a molecular level and in vitro UVA‐1 irradiation was realized on lesional fibroblasts primary cultures. Results: The LoSCAT and the DLQI showed to decrease significantly starting from the last UVA‐1 session. A significant reduction in muscularis fascia thickness (−50% on average) was estimated starting from 3 months after the last UVA‐1 session and maintained up to 12 months follow‐up. Tissues was detected by HRUS. The UVA‐1 in vitro irradiation of lesional skin sites cells appeared not to affect their viability. Molecular genes analysis revealed a significant reduction of IL‐1ß and of TGF‐ß genes after phototherapy, while MMPs 1, 2, 9 gene expression was enhanced. Comment: These preliminary in vivo and in vitro findings suggest that UVA‐1 phototherapy is a safe and useful adjuvant therapy able to elicit anti‐inflammatory effects and stimulate tissue matrix digestion and remodeling at lesional sites.